(3MOjK eMeO Hf YHO Gddg GdCfUGQi hahGFO CHj eMeO Hf eGS GdHRGRs - (3GddLjs
(3ChdgG (B:s
(3MOjK GdCfUGQi Yf SdjeGf GdJjei (B: (3CNHQfG GdTjN YHO GdYRjR Hf eMehO Hf GdeHGQc GdMGaX bGd QShd Gddg Udi Gddg Ydjg hSde (B: (3dG gLQI Hjf GdedSejf ahb KdGKI CjGe s
(3BNQgG (B:s
(3ef MOjK CHj HcQ GdUOjb QVi Gddg Yfg (B: (3aEf GSJbeJ aGJHYhfi hEf RZJ abhehfi BNQ GdLRA s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeMehOjI (B- (3HecJHI GdeOjfI GdefhQI GdYGeI(B((3eLGejY (B124) s
Keywords: (3GdMOjK h GdeUWdMs